The Effect of Credit Risk, Liquidity Risk, And Market Risk on Financial Performance In Banking Companies Listed on The Indonesia Stock Exchange - Apolonia Nurmida De Arfa; Nur Ida Iriani; Imam Hidayat (International Research & Development for Human Beings (IRDH), 2026)
Market risk is represented by the Net Interest Margin (NIM), where fluctuations in NIM can affect a bank’s net interest income and, in turn, its overall financial performance. This study examines the effects of credit risk, liquidity risk, and market risk on the financial performance of banks listed on the Indonesia Stock Exchange (IDX). A quantitative approach is employed using secondary data derived from the annual financial statements of selected banks. The sample is determined through purposive sampling based on predefined criteria. Data are analyzed using multiple linear regression with the support of statistical software. The findings indicate that credit risk negatively affects financial performance, as higher credit risk reduces corporate outcomes. In contrast, liquidity risk positively influences financial performance, with increased liquidity risk associated with improved financial results. Market risk, however, exerts a negative impact, meaning that greater market risk leads to weaker corporate performance. Furthermore, hypothesis testing confirms that credit risk, liquidity risk, and market risk collectively have a significant effect on financial performance, underscoring the importance of comprehensive risk management in sustaining stability and long-term performance.